Ilhas, do lado de lá da rua - reflexões sobre a habitação popular e social e a sua integração na cidade do Porto - Beatriz Rodrigues Gomes de Almeida (2015)
"Ilhas" is the name given to the clusters created by the long and narrow corridors that create the only facade of the small one floored houses, they appear in Oporto as consequence of an enormous demographic growth in the city. These complexes gave lodging to the rural population that arrived to the already overcrowded city. Being a low risk investment that involved very little resources and gave new use to the long empty lands in the back of the bourgeois houses this type of construction expanded all through the city. Having these fields little market value it was possible for the proprietor to charge low incomes, making the "Ilhas" the shelter of the lower working classes. Similarly to other types of working classes houses, the "Ilhas" had many sanitary problems. Having a single front and being that front faced to the narrow corridor it was only natural that these places had ventilation and insolation problems, turning these clusters into dark and unhealthy places, focus of several diseases. With more than a century of existence this spaces where continually object of actions that mainly had as directive the demolition and extinction of these spaces. Today the city counts almost a thousand "Ilhas", most of them being in bad condition making them a problem worth of some attention. With the analyses presented here one tries to understand the history of these places, how they are part of the contemporary city and how Porto has dealt and is dealing with the "Ilhas."